2016
DOI: 10.1111/jop.12504
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of BRAF V600E (VE1) protein expression and BRAF gene mutation status in codon 600 in benign and malignant salivary gland neoplasms

Abstract: In studied salivary gland cancers, no PCR-based prove mutations of BRAF V600 were detected. Further molecular analyses are necessary to rapid molecular arrays for the identification of specific mutations, optimal for individualized targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Immunohistochemical staining was carried out as described elsewhere [ 14 16 ], and the results were standardized against a series of positive and negative controls. Positive control staining was performed on a model tissue section selected according to The Human Protein Atlas ( http://www.proteinatlas.org ) [ 17 ] and antibody specification (Additional file 1 : Table S1) and the antibody datasheet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining was carried out as described elsewhere [ 14 16 ], and the results were standardized against a series of positive and negative controls. Positive control staining was performed on a model tissue section selected according to The Human Protein Atlas ( http://www.proteinatlas.org ) [ 17 ] and antibody specification (Additional file 1 : Table S1) and the antibody datasheet.…”
Section: Methodsmentioning
confidence: 99%
“…Each slide was examined under ECLIPSE E400 light microscope (Nikon Instruments Europe, Amsterdam, Netherlands) with the low-power (20×) objective. The result of immunohistochemical staining was expressed according to Immunoreactive Remmele-Stegner (IRS) score [ 18 ], described in detail in our previous papers [ 14 16 , 19 ]. Total IRC score (from 0 to 12) was obtained by multiplying the staining intensity score (0—negative, 1—weak staining, 2—moderate staining, 3—strong staining) by the relative proportion of immunolabeled specimen area (0—none; 1—less than 10%; 2—10 to 50%; 3—50 to 80%; 4—at least 80%).…”
Section: Methodsmentioning
confidence: 99%
“…Bodnar et al showed that some salivary gland neoplasms had either nuclear or cytoplasmic expression of BRAF V600E protein on IHC analysis. However, their polymerase chain reaction‐based studies did not detect a corresponding mutation 11 …”
Section: Discussionmentioning
confidence: 96%
“…The immunohistochemical staining was performed according to previously described procedures [34, 35] and standardized using a series of positive and negative control reactions. The positive control reaction was performed on a model tissue selected according to reference sources (The Human Protein Atlas, http://www.proteinatlas.org) [36] and the antibody datasheets.…”
Section: Methodsmentioning
confidence: 99%